2019
DOI: 10.1017/prp.2019.6
|View full text |Cite
|
Sign up to set email alerts
|

A computerized adaptive testing advancing the measurement of subjective well-being

Abstract: This article aimed at developing an adaptive version of the subjective well-being (SWB) scale to measure a comprehensive concept of SWB among Chinese university students. Item response theory was employed to formulate the item bank of the SWB scale and computerized adaptive testing (CAT) for SWB (CAT-SWB), based on several commonly used SWB scales, after unidimensionality testing, model selection, local dependence testing, parameter estimation, item fit test and differential item functioning (DIF) analysis wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…If the ratio of the first eigenvalue explanatory variance to the second eigenvalue explanatory variance is greater than 4 and the variance of the first factor interpretation is greater than 20% (Reckase, 1979), the data can be considered to basically conform to this assumption (Reeve et al, 2007). Some researchers (Wu et al, 2019; Zhang et al, 2019) have tested this assumption according to the abovementioned standards when developing a unidimensional CAT item bank. In this part, we evaluate the dimensionality of our item bank using exploratory factor analyses via the SPSS 20.0 software by the following procedure.…”
Section: Discussionmentioning
confidence: 99%
“…If the ratio of the first eigenvalue explanatory variance to the second eigenvalue explanatory variance is greater than 4 and the variance of the first factor interpretation is greater than 20% (Reckase, 1979), the data can be considered to basically conform to this assumption (Reeve et al, 2007). Some researchers (Wu et al, 2019; Zhang et al, 2019) have tested this assumption according to the abovementioned standards when developing a unidimensional CAT item bank. In this part, we evaluate the dimensionality of our item bank using exploratory factor analyses via the SPSS 20.0 software by the following procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Sessions are typically logged in order to provide detailed feedback to therapists. On the cognitive side, these adaptive systems have been designed to evaluate subjective well-being (Wu et al . 2019) and phonological acquisition (Origlia et al .…”
Section: Gamificationmentioning
confidence: 99%
“…To confirm the unidimensionality of the selected items from seven scales, we first conducted a one-factorial exploratory factor analysis (EFA) to eliminate items with factor loadings less than 0.40 at a time (Wu et al, 2019). This approach was supported by Nunnally's (1978) conclusions, which suggested that factor loadings smaller than 0.30 should not be taken seriously and that factor loadings smaller than 0.40 can easily be overinterpreted.…”
Section: Unidimensionalitymentioning
confidence: 99%